PERSEPSI PEROKOK SURABAYA TERHADAP PESAN IKLAN LAYANAN MASYARAKAT MENGENAI BAHAYA MEROKOK - Novia Puspita Putri (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
The age of active smokers in Indonesia is getting younger. Riskesdas (2013) states that the age of the first smoking population of Indonesia is the most aged 15-19 years, which amounted to 55.4%. WHO (2011) states that this time in every year there are 6 million of people dying from smoking habit. WHO predicts on 2030 there will be an increase in cases to 8 million deaths due to smoking. To eliminating this problem, the Ministry of Health of the Republic of Indonesia has launched a public service advertisement about the dangers of smoking. Therefore, this study aims to analyze the perception of teenage smokers in Surabaya against to public service advertisement based on the theory of Extended Parallel Process Model. This research uses descriptive qualitative  method. Data collection was done by in-depth interviews, with the help of interview guidelines. This research was conducted in Surabaya city, with 8 informants. The results of the study indicate that all informants have felt the fear and the severity element presented by the public service advertisement. But not all informants have sensed the vulnerability, confidence, and beliefs of the responses presented in the content of public service advertisement. In the element of belief response, based on the results of research, it was found that not all informants feel motivated to quit smoking after seeing the public service advertisement. Therefore, to increase the belief of active adolescent smokers to quit smoking, the need for visualization development of public service advertisements that has been made.Keyword: smoking, adolescence, public service advertisement,  Extended Parallel Process Model (EPPM)